CO2 MONITORING PREDICTION BY USING FORWARD MODELING SEISMIC TIME LAPSE WITH DATA FROM SIMULATION RESERVOIR RESULT: CASE STUDY OF GUNDIH PILOT PROJECT CARBON STORAGE, INDONESIA - RATNA KUSUMARTINI ASIKIN (NIM: 32312002), ARIESTY
Carbon Capture Storage (CCS) otherwise known as Carbon Sequestration is one of the methods used to reduce atmospheric CO2 levels. This research was conducted at Gundih Field in Central Java as Pilot Project Carbon Storage in Indonesia. Indonesia has many active oil and gas field that produce CO2 as residual gas production. The Central Processing Plant (CPP) is available on the Gundih field for the separation between production gas and residual gas. To date, these CO2 gases are flared into the atmosphere thus increasing the CO2 emission. With this research, it is expected to be a reference for further CCS study in Indonesia and carbon storage method may be applied in those fields. This study is divided into three main stages: reservoir characterization, reservoir injection simulation and forward modeling seismic time lapse to predict CO2 movement in the earthÃ‚Â’s subsurface after injection. The reservoir characterization process is an important first step to assess the feasibility of the target reservoir. A closed structure is sought in this step to be the CO2 trap in the subsurface. From the two areas that have been evaluated which are Gundih Field itself and the Jepon-1 Well area, an anticline were found to be the CO2 injection target. Geological models are constructed with limited quantity of seismic and well data to obtain the physical properties information in the reservoir. The distribution of porosity, permeability and water saturation that has been examined in the four sand layer targets by using an acoustic impedance inversion show good criteria to be the CO2 injection target layer, especially in Sand B layer as our main target. The calculation of reservoir volume is also performed using two different approaches to prevent excessive subsurface injection. The result of the reservoir characterization process will be the input data on the CO2 injection simulation process. Nine reservoir simulation scenarios were performed with a certain rate and length of injections. The rate and duration of the injection are made differently in each case to see the possible changes in the reservoir due to the injection process. The analysis of CO2 deployment in the reservoir was conducted to see the effect of the injection especially on changes in pressure and water saturation and CO2 saturation. The simulation results show that when larger quantities of CO2 are injected into the target reservoir, it will migrate to the top of the anticline structure located to the southeast of the CO2 injection well. CO2 displacement in the simulation shows that the injected CO2 will not reach the fault location near the Jepon-1 well. From the reservoir simulation analysis, a synthetic geological model that describes the condition before and after the injection occurs. The furthest distant of CO2 displacement was calculated in two scenarios: the smallest and largest injection cases and described as CO2-saturated layer. Forward modeling is done on those models to produce a synthetic seismic section. Synthetic seismic acquisitions are designed with 2 different frequencies to produce synthetic seismic which could map the thin layer sand reservoir. The section differences from before and after the injection process section was evaluated and the seismic parameters which are sensitive to CO2 injections were analyzed. The amplitude differences generated from both models could describe the effect of CO2 injection. In addition, the Amplitude Versus Offset (AVO) section can also see the presence of CO2 in the subsurface.